2014
DOI: 10.1093/jac/dkt534
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of baicalin against influenza virus H1N1-pdm09 is due to modulation of NS1-mediated cellular innate immune responses

Abstract: Overall, this study highlights that baicalin exerts its anti-influenza virus activity by modulating viral protein NS1, resulting in up-regulation of IFN-induced antiviral signalling and a decrease in PI3K/Akt signalling in cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 70 publications
1
78
1
1
Order By: Relevance
“…Baicalin was able to induce the production of interferon-gamma (IFN-ɣ) in natural killer (NK), CD4+ and CD8+ T cells during in vitro influenza A virus infection. It was suggested that baicalin was able to directly bind NS1-p85β (RNA binding domain), which was the main mediator to downregulate IFN-ɣ [15]. The induction of IFN-ɣ triggered the immune system to activate the Janus kinase/signal transducer and activator of transcription protein 1 (JAK/STAT1) pathway, which led to the expression of IFN-ɣinducible genes.…”
Section: Flavonoids Against Non-picornavirusesmentioning
confidence: 99%
“…Baicalin was able to induce the production of interferon-gamma (IFN-ɣ) in natural killer (NK), CD4+ and CD8+ T cells during in vitro influenza A virus infection. It was suggested that baicalin was able to directly bind NS1-p85β (RNA binding domain), which was the main mediator to downregulate IFN-ɣ [15]. The induction of IFN-ɣ triggered the immune system to activate the Janus kinase/signal transducer and activator of transcription protein 1 (JAK/STAT1) pathway, which led to the expression of IFN-ɣinducible genes.…”
Section: Flavonoids Against Non-picornavirusesmentioning
confidence: 99%
“…The NS1 protein has been identified as a potential drug target (Maroto, Fernandez et al 2008;Basu, Walkiewicz et al 2009;Jablonski, Basu et al;Walkiewicz, Basu et al 2011). Previous studies on potential ligand binding sites in influenza NS1 identified 2 sites in the RNA binding domain that would interact with R35 or D39 (Darapaneni, Prabhaker et al 2009), and at least one potential drug, baicalin has been shown to interact with R35, R38, and D39 (Nayak, Agrawal et al 2014)…”
Section: Discussionmentioning
confidence: 99%
“…Recent, studies have reported that baicalin regulates Toll-like receptors (TLRs) [15], NOD-like receptors (NODR) and other immune receptors in the innate and adaptive systems [16]. Previous studies have also suggested that LYSO can enhance the activity of some antibacterial drugs [17].…”
Section: Introductionmentioning
confidence: 99%